Síntese, caracterização e avaliação das propriedades térmicas e óticas de cristais líquidos discóticos derivados de azo-2,3-difenilquinoxalinas - Silva, Welisson de Pontes (2018)
Liquid crystals (LCs) are important materials with properties of order and fluidity. The control of self-organization and self-assembly characteristics can be performed by the introduction of optical switch, such as an azobenzene system. Luminescent and charge-carrying properties can be aggregated by the incorporation of the quinoxaline center. In this context, this dissertation presents the synthesis and characterization of the mesomorphic and optical properties of four series of 1,4-disubstituted azobenzenederived compounds connected to the quinoxaline center. The molecules are constituted by the azobenzene rigid center, where groups with different polarities, sizes and electronic properties, such as OC10H21, NO2, Cl, OCH3 and OC8H17 (branched alkoxy chain) groups were introduced at one end. At the other end, the quinoxaline center is substituted at the 2,3-positions with methoxyphenyl or dodecyloxyphenyl groups. To link the azobenzene system to quinoxaline the ester group was used, which can be directly or using a six carbon spacer group. The compounds were characterized by infrared spectroscopy, 1H and 13C nuclear magnetic resonance and mass spectrometry. The mesomorphic properties were investigated by Polarized Optical Light Microscopy (MOLP), Differential Scanning Calorimetry and X-ray diffractometry (XRD) at different temperatures. The results showed that the dodecyloxyphenyl groups in the quinoxaline moiety and compacts electron withdrawing groups in the azobenzene system favored the stabilization of the columnar mesophase while the methoxyphenyl groups in quinoxaline moiety were determinant in generation of materials that do not present crystallization in cooling, remaining as a solid isotropic glass. The compounds presented low luminescence in the blue region with higher intensities for the compounds with the six carbon spacer group. The compounds presented low luminescence in the blue region with higher intensities for the compounds with the six carbon spacer group due to the greater intramolecular distance of the azobenzene and quinoxaline chromophores. The compounds showed reversible photoisomerization in solution and also in mesophase evaluated by MOLP and XRD.